The Effectiveness of Group Guidance with Shame Attacking Exercise to Improve Students’ Assertive Behavior - Feby Amanda HLM; Irwan S (MASI Mandiri Edukasi, 2025)
This study aims to determine the effectiveness of group counseling services using the Shame Attacking Exercise technique in enhancing the assertive behavior of eighth-grade students at UPT SMP Negeri 27 Medan. The study employed a quasi-experimental design with a non-equivalent control group, involving 16 students with low assertive behavior, divided into experimental and control groups. The experimental group received an intervention consisting of six group counseling sessions using the Shame Attacking Exercise technique, while the control group participated in regular group guidance. Data were collected using an assertive behavior scale and analyzed with normality tests, homogeneity tests, and paired sample t-tests. The research results showed a significant increase in assertive behavior in the experimental group (post-test mean = 97, high category), compared to the control group (post-test mean = 89, medium–high category), with a significance value of 0.001 < 0.05. These findings confirm that the Shame Attacking Exercise technique is effective in helping students express themselves assertively, honestly, and confidently. This study has implications for guidance counselors, school counselors, and parents in supporting the development of students' assertive behavior. The study's limitations include a small sample size and a short intervention duration; therefore, further research is recommended with a larger sample and a mixed-methods approach to strengthen the generalizability of the results.